RESPON MASYARAKAT TERHADAP SAYUR ORGANIK DI KOTA MALANG - Dicky Efendi; Bambang Siswadi; Masyhuri Mahfudz (Program Studi Agribisnis, 2019)
AbstracThis study aims to 1. Know the response of the community towards organic vegetables 2. Social economic factors that influence the community's response to organic vegetables Determination of the location of this study is purposive, at the SuperIndo Tlogomas Shopping Center and CV. Kurnia Kitri Ayu in Malang City. In the study obtained a sample of respondents who bought organic vegetables as many as 30 people and samples from organic vegetable respondents, the total respondents obtained from this study were as many as 448 respondents. On the results of the analysis using the logit test, factors that influence people's perceptions of organic vegetables include: health variables have an average of 19.75, a quality variable with an average of 15.5, a price variable with an average of 15.25, and environmentally friendly variables and security variables each have an average score of 15.5 and 4.5. Whereas the factors that influence the community's response to organic vegetables in the poor city are education, income, distance of place and frequency of promotion while age, number of family dependents and perceptions do not significantly influence the community response to organic vegetables.